Environment and mate attractiveness in a wild insect. (26th July 2022) - Tregenza, Tom; Niemelä, Petri T; Rodríguez-Muñoz, Rolando; Hopwood, Paul E
Abstract: The role of female choice in sexual selection is well established, including the recognition that females choose their mates based on multiple cues. These cues may include intrinsic aspects of a male's phenotype as well as aspects of the environment associated with the male. The role of the spatial location of a potential mate has been well studied in territorial vertebrates. However, despite their role as laboratory models for studies of sexual selection, the potential for insects to choose their mates on the basis of location has scarcely been studied. We studied a natural population of individually tagged crickets (Gryllus campestris) in a meadow in Northern Spain. Adults typically move between burrows every few days, allowing us to examine how pairing success of males can be predicted by the burrow they occupy, independent of their own characteristics. We observed the entirety of ten independent breeding seasons to provide replication and to determine whether the relative importance of these factors is stable across years. We find that both male ID and the ID his burrow affect the likelihood that he is paired with a female, but the burrow has a consistently greater influence. Furthermore, the two factors interact: the relative attractiveness of an individual male depends on which burrow he occupies. Our finding demonstrates a close interaction between naturally and sexually selected traits. It also demonstrates that mate choice studies may benefit from considering not only obvious secondary sexual traits, but also more cryptic traits such as microhabitat choice. Abstract : We show that female insects choosing to cohabit with a male place more importance on where he lives than on who he is, but the combination of the two is more important still. We know that female birds often choose a male based on the quality of his territory; our 10 years of observing crickets moving around a Spanish meadow to share burrows with members of the opposite sex, reveals insects can do the same.